Designation of pathogenic resistant bacteria in the Sparusaurata sea collected in Tunisia coastlines: Correlation with high performance liquid chromatography-tandem mass spectrometry analysis of antibiotics. (May 2017) - Zouiten, Amina; Mehri, Ines; Beltifa, Asma; Ghorbel, Asma; Sire, Olivier; Van Loco, Joris; Abdenaceur, Hassen; Reyns, Tim; Ben Mansour, Hedi
Abstract: Vibrio is characterized by a large number of species and some of them are human pathogens causing gastro intestinal and wound infections through the ingestion or manipulation of contaminated fishes including Vibrio parahaemolyticus and Vibrio alginolyticus . In this study, we reported the phenotypic and molecular characterization of Vibrio parahaemolyticus and Vibrio alginolyticus strains isolated from wild and farm sea bream ( Sparus aurata L.) along the Tunisian coast from December 2015 to April 2016. Therefore, the antibiograms indicate a difference between farmed and wild fish. Resistance against amoxicillin antibiotic appears for the bacteria isolated from wild fish, while those from aquaculture farming presented sensitivity to amoxicillin and resistance to antibiotics colistin and fusidic acid. The chloramphenicol antibiotic exhibited a high sensitivity in all isolated bacteria. In fact, traces of amoxicillin in the organs of the fish from Hergla farm were detected by UPLC-MS/MS analysis during December 2016 to April 2016. In addition, antibiotics were detected in January 2014 with high concentration of norfloxacin 2262 ng/g in fish from Hergla coast. The results obtained in this work indicated that the use and presence of antibiotics in water impacts on the occurrence of resistant bacteria and the detection of antibiotic in fish. Highlights: Wild and Farmed fish contaminated with Antibiotics. Pathogenic resistant bacteria infect fish in different Tunisian Coastlines. Development of the UPLC-MS/MS for detecting antibiotics.